Protein stabilization by RSUME accounts for PTTG pituitary tumor abundance and oncogenicity. Issue 6 (June 2018) - Fuertes, M; Sapochnik, M; Tedesco, L; Senin, S; Attorresi, A; Ajler, P; Carrizo, G; Cervio, A; Sevlever, G; Bonfiglio, J J; Stalla, G K; Arzt, E
Abstract : Increased levels of the proto-oncogene pituitary tumor-transforming gene 1 (PTTG) have been repeatedly reported in several human solid tumors, especially in endocrine-related tumors such as pituitary adenomas. Securin PTTG has a critical role in pituitary tumorigenesis. However, the cause of upregulation has not been found yet, despite analyses made at the gene, promoter and mRNA level that show that no mutations, epigenetic modifications or other mechanisms that deregulate its expression may explain its overexpression and action as an oncogene. We describe that high PTTG protein levels are induced by the RWD-containing sumoylation enhancer (RWDD3 or RSUME), a protein originally identified in the same pituitary tumor cell line in which PTTG was also cloned. We demonstrate that PTTG and RSUME have a positive expression correlation in human pituitary adenomas. RSUME increases PTTG protein in pituitary tumor cell lines, prolongs the half-life of PTTG protein and regulates the PTTG induction by estradiol. As a consequence, RSUME enhances PTTG transcription factor and securin activities. PTTG hyperactivity on the cell cycle resulted in recurrent and unequal divisions without cytokinesis, and the consequential appearance of aneuploidies and multinucleated cells in the tumor. RSUME knockdown diminishes securin PTTG and reduces its tumorigenic potential in a xenograft mouse model. Taken together, our findings show that PTTG high protein steady state levels account for PTTG tumor abundance and demonstrate a critical role of RSUME in this process in pituitary tumor cells.